Determining the speed and acceleration of the separator for grass leaf part in horizontal and vertical directions - Abilzhanuly, Tokhtar; Keshuov, Seitkazy; Rzaliyev, Askar; Zhortuylov, Omirserik; Zhumatay, Gani; Abilzhanov, Daniyar; Karmanov, Darkhan; Boranbayev, Bauyrzhan (Eastern-European Journal of Enterprise Technologies, 2021)
Vitamin-grass flour is the main component of mixed fodders intended for all types of livestock and poultry. Earlier and currently, the vitamin-grass flour has been prepared from legumes by a high-temperature drying technique. However, existing techniques have high operating costs and require very expensive technical tools. To reduce the specific operating costs and the price of equipment in the production of VGF, a technique has been proposed that involves the main drying of grass to a moisture content of 30‒35 % on a swath while the post-drying of grass is performed in a small-sized channel under the haystack without air heating. Next, the dried mass is pre-crushed. At the same time, the delicate leaf part of the hay, while falling between the side walls of hammers and counter-hammers, is ground and finely crushed, and the stems are processed into large fractions. From pre-crushed hay, the leaf part is separated and fed into the crusher to produce flour. In this case, the main machine that determines the performance of the line is the separator of the leaf part of the grass. The results of the theoretical research have established the speed and acceleration of hay movement on the surface of the sieve. These values determine the productivity of separation of the leaf part from pre-crushed hay and the reliability of the selected structural and technological scheme of the separator. The production tests have confirmed the reliability and economic efficiency of the proposed technique. Comparing the proposed technique for obtaining vitamin-grass flour by existing high-temperature methods has shown that the carotene content in flour was 1.6 times higher while the specific operating costs and equipment price were 6‒7 times lower